2A.04: WHETHER ACE INHIBITOR/ARB COMBINED WITH CCB IS SUPERIOR TO OTHER COMBINATIONS? A META-ANALYSIS IN 20, 669 HYPERTENSIVES. (June 2015) - Chi, C.; Tai, C.; Wang, J.; Protogerou, A.; Blacher, J.; Safar, M.E.; Zhang, Y.; Xu, Y.
Abstract : Objective: Current clinical evidence and latest guidelines recommended the combination antihypertensive therapy with angiotensin-converting enzyme (ACE) inhibitor / angiotensin receptor blocker (ARB) and calcium channel blocker (CCB) in patients with grade 2 to 3 hypertension. However, data are scarce in the comparison between the ACE inhibitor / ARB + CCB (A+C) therapy and other combinations. We therefore conducted a meta-analysis to see if ACE inhibitor/ARB combined with CCB is superior to other combinations. Figure. No caption available. Design and method: A meta-analysis was conducted in 20, 669 hypertensives from 9 randomized controlled trials and we compared the A+C therapy with other combinations, in terms of blood pressure (BP) reduction, clinical outcomes and adverse effects. Results: BP reduction did not differ significantly between the A+C therapy and other combination therapies, neither in systolic nor in diastolic BP, with P = 0.43 and P = 0.41, respectively. However, A+C strategy, compared with other combination therapies, achieved a significantly lower incidence of cardiovascular composite endpoints, including cardiovascular mortality, non-fatal myocardial infarction and non-fatal stroke (Risk ratio [RR] and 95% confidential interval [CI]: 0.80 [0.70, 0.91], P < 0.001, see as Figure), but similar all-cause mortality (0.90 [0.77, 1.04], P = 0.15) and stroke rate (0.90 [0.77, 1.04], P = 0.09). Moreover, A+C combination therapy exhibited a 3.10 ml/min/1.73m2 greater estimated glomerular filtration rate than other combinations (P = 0.01). Lastly, A+C therapy showed a similar incidence of adverse effects as other combinations (P = 0.34), but had a significantly lower incidence of severe adverse effects (0.85 [0.73, 0.98], P = 0.03). Conclusions: In summary, clinical evidences favor A+C therapy, which is superior to other combinations, in current anti-hypertensive strategy, with greater clinical benefit in cardiovascular outcome and reservation of renal function.